IoT Based Durian Tree Monitoring System - Teo, Yi Ming; Zainal, Shamian (Progress in Engineering Application and Technology, 2022)
Due to the rapid advancement of Internet of Things in the 5G era, modern IoT for agriculture has starting replaced the traditional way of monitoring and irrigation for agriculture. With the implementation of the IoT in agriculture, the farmers can real-time monitoring their durian trees. The farmers can easily watch the tree's health parameters from cloud-based data. The farmers can know the condition of the trees in real-time such as the temperature of the environment, humidity of the environment, and soil moisture. The real-time data will be displayed by a chart and makes the farmers can watch the data conveniently. Besides that, the irrigation system can automatically detect the soil moisture and select the suitable time to water the durian trees. At the same time, for the traditional method of irrigation, most of the farmers need to water the trees by themselves. Meanwhile, the large-size durian farm requires more manpower to manage the field and there is not guarantee all the trees can be watering. Furthermore, this IoT system requires a power supply for the Raspberry Pi and sensors to work. Rural areas like durian farm do not have an On-Grid power supply. Therefore, the farmers need solar power system for generate electricity. A solar system is the most convenient power supply for the durian farm. To conclude, this project is suitable for the farmers to watch the health parameter of the durian tree, irrigation system for the farmers can reduce the manpower cost and solar system is the portable energy for the rural areas.